Centromeric Histone H3 Is Essential for Vegetative Cell Division and for DNA Elimination during Conjugation in Tetrahymena thermophila - Cui, Bowen (American Society for Microbiology, 2006)
The Tetrahymena thermophila CNA1 gene encodes the centromeric H3, Cna1p. Green fluorescent protein (GFP)-tagged Cna1p localizes in micronuclei in dots whose number and behavior during mitosis and conjugation are consistent with centromeres. During interphase, Cna1p-GFP localizes in peripheral dots, suggesting centromeres are associated with the nuclear envelope. Newly synthesized Cna1p-GFP enters micronuclei in mitosis and accumulates in the nucleoplasm. Its deposition at centromeres starts at early S phase and continues through most of S phase. CNA1 is required for vegetative cell growth. Knockdown of CNA1 genes in the somatic macronucleus results in micronuclear DNA loss and delayed chromosome segregation during mitosis. During conjugation, Cna1p-GFP disappears from the centromeres in the developing macronucleus, consistent with centromeric sequences being internal eliminated sequences. Surprisingly, zygotic CNA1 is required for efficient elimination of germ line-specific sequences during development of the new macronuclei but not for the RNA interference pathway, through which sequences are targeted for elimination. Zygotically expressed Cna1p localizes in the spherical structures in which the later stages of DNA elimination occur, and these structures cannot be formed in the absence of zygotic CNA1, suggesting that, in addition to functioning in centromeres, Cna1p may also play a role in organizing the formation of the DNA elimination structures.